Answer:
(6, -9)
Explanation:
Eliminate y (you can do x too, but y is easier for this problem)
To eliminate y we must get 0y
If one is 2y, the other must be -2y to get to 0
Keep the first equation the same
7x + 2y = 24
Multiply all numbers in the second equation by -2 (so y can be -2y)
-8x + -2y = -30
Positive + Negative = Negative
-8x - 2y = -30
Now add/subtract the two equations from each other
7x + 2y = 24
-8x - 2y = -30
-1x + 0y = -6
-1x = -6
Divide both sides by -1 to isolate variable
-1x ÷ -1 = -6 ÷ -1
x = 6
We could simply plug in the x value into one of the equations, but that's substitution - not elimination. Repeat the same steps for x
I will multiply the first equation by 4 to get 28x and the second equation by -7 to get -28x for an answer of 0x
28x + 8y = 96
-28x - 7y = -105
0x + 1y = -9
1y = -9
Divide both sides by 1 to isolate the variable
1y ÷ 1 = -9 ÷ 1
y = -9